Theoretical and numerical studies of elastic buckling and load resistance of double cross-arm pre-tensioned cable stayed buckling-restrained braces. (15th December 2017) - Guo, Yan-Lin; Zhou, Peng; Andrew Bradford, Mark; Pi, Yong-Lin; Tong, Jing-Zhong; Fu, Peng-Peng
Highlights: A double cross-arm pre-tensioned cable stayed buckling-restrained brace (DPCS-BRB) is proposed. Elastic buckling behaviour and load resistance of the DPCS-BRB are investigated. Single-wave symmetric or double-wave antisymmetric buckling mode exists in the DPCS-BRB. Optimal location of the cross-arms is explored through FE analysis. A lower limit of restraining ratio of DPCS-BRB is obtained for reaching a core compressive strain of 2%. Abstract: This paper investigates the elastic buckling behaviour and load resistance of a double cross-arm pre-tensioned cable stayed buckling-restrained brace (DPCS-BRB) where an extra cross-arm is assigned within a longitudinal cable truss along its length. Naturally, the span and efficiency of the PCS-BRB can be increased and improved by adopting multiple cross-arms. Equilibrium method is utilised to derive the formula of elastic buckling load of a pin-ended DPCS-BRB, and the obtained results have been verified through FE analysis. It is found from theoretical derivations and FE analysis that there exists a single-wave symmetric and double-wave antisymmetric buckling modes in the DPCS-BRB, respectively. In addition, a negative linear correlation exists between the elastic buckling load and the initial pre-tensioning force of the cables in the DPCS-BRB. Furthermore, it has been explored through FE analysis that the optimal location of the cross-arms for achieving higher elastic buckling load as well as higher ultimate compressive load-carrying capacity is found to be a quarter length to each end of the DPCS-BRB. At last, the ultimate compressive load-carrying capacity of the DPCS-BRB is found to be directly proportional to its restraining ratio, and there exists a lower limit of the restraining ratio which ensures the core could reach its full cross-sectional yield load without overall instability of the DPCS-BRB. The investigation of the elastic buckling behaviour and ultimate compressive load-carrying capacity as well as the failure mechanism of the DPCS-BRB provides fundamentals to the further development of a comprehensive design method of the DPCS-BRB subjected to axial cyclic loads.